Aplikasi Game Checkers Menggunakan Metode Alpha Beta Dan Minimax - Givan, Muhammad; Wafiah, Andi (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
One option for fun when hanging out with friends is to play checkers. Playing the game, meanwhile, may be made more difficult by its limits. The purpose of this study is to create a checkers gaming application based on the Alpha Beta and Minimax algorithms. Experimental research methods and literature review were used to collect data over a two-month period. Analysis utilizing the programming language PHP, Javascript, Web Server, Editor Visual Studio Code, and white box testing with the result V(G) = 5, as well as black box testing, reveal that the function performance is consistent with F0 logic. The study results of the Checkers Game Application give a playing experience that is tough, enjoyable, and pleasant to use rather than utilizing the physical.